Making a prototype of the Fuel Pump Test Bench with a method of measuring fuel pressure, current and temperature of a microcontroller-based fuel pump - Rosadi, Ajib; Satmoko, Ambar Wanto; Afani, Randy Putra (International Journal Labs, 2023)
The object of this research is a vehicle with a fuel injection system and uses a fuel pump to produce pressurized fuel. The fuel pump has decreased performance for some time of use. Decreased performance is characterized by abnormal engine power. But these symptoms can also be caused by other factors such as disturbances in the ignition system, fuel system or air intake system. To obtain the true causative factors by the workshop, a comprehensive examination of related systems is carried out. F the causative actor in the fuel system is the fuel pump, then the action taken by the workshop is replacement. In two-wheeled vehicles, fuel pump replacement is carried out after the fuel pump cannot operate. While four-wheeled vehicles, fuel pump replacement is recommended every 80,000 km. From the average data of Astra workshops that the number of vehicles that replace fuel pumps is 3 to 4 units within one month. Based on the procedure for checking the condition of the Astra vehicle fuel pump, which only measures fuel pressure and the resistance value of the fuel pump coil. The standard fuel pressure value is 2.94 bar and the fuel pump coil resistance value is 0.8 ohms. The measurement of the 2 parameters does not represent the actual condition of the fuel pump, whether the fuel pump can still be used or must be replaced. According to Denton in a book entitled Automobile Electrical and Electronic System Fourth Edition (2012) that the right fuel pump testing method must be with manufacturing standards, namely a flow discharge of 120 liters per hour with pressure conditions of 3 bar, source voltage of 12 volts, coil resistance of 0.8 ohms and maximum current to the coil of 10.5 amperes. As a solution to determine whether the fuel pump can still be used or must be replaced, it is necessary to make a fuel pump test bench with a method of measuring fuel pressure, current and fuel pump temperature. In order for all measurable parameters to be displayed into a conclusion, this tool is made based on microcontrollers. This fuel pump test bench can be used to determine the condition and predict the age of the fuel pump.